IMPLEMENTATION OF ONLINE BIRTH CERTIFICATE SERVICES THROUGH THE CLAMPID AT THE CANTIAN DISTRICT OFFICE OF CANTIAN SURABAYA CITY - Anwar, Achmad Mubarok (MAP Observer: Jurnal Penelitian Administrasi Publik, 2022)
Public service is the fulfillment of the basic rights of citizens by the government, one example of public service is population administration such as administering birth certificates. Pabean Cantian Sub District as the organizer of population administration, especially birth certificates by utilizing technology via Klampid on the E-Kios machine, which is an electronic media that functions to facilitate services to the community. The purpose of the study was to determine the application of birth certificate services via Klampid at the Sub District Office of Pabean Cantian, Surabaya City and to find out what the supporting factors and inhibiting factors were. The type research used is descriptive qualitative method. Meanwhile, the focus of the research is using the concept of the Surat Keputusan MENPAN Nomor 63 Tahun 2003 concerning the Principles of Public Service. The results showed that the implementation of Birth Certificate Services via Klampid at the Sub District Office of Pabean Cantian, Surabaya City was in a good category on the indicators of Simplicity, Security, Responsibility, Time Certainty, Discipline, Politeness and Hospitality, while the indicators of Completeness of Facilities and Infrastructure were still not good.